2021
DOI: 10.1021/acsami.1c08810
|View full text |Cite
|
Sign up to set email alerts
|

Anchored Pt-Co Nanoparticles on Honeycombed Graphene as Highly Durable Catalysts for the Oxygen Reduction Reaction

Abstract: Durability is an important factor in evaluating the performance of a catalyst. In this work, the spatial protection of the carrier to nanoparticles was considered to improve the durability of the catalyst. It is found that a honeycombed graphene with a three-dimensional (3D)-hierarchical porous structure (3D HPG) can help to reduce the shedding of Pt-Co nanoparticles (Pt-Co NPs) because 3D HPG can form a protective layer to reduce the direct erosion of Pt-Co NPs on the interface by an electrolyte. Then, approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…The application of these materials is diverse, but the literature shows that the main interests are for the increase of surface area, porosity or just general improvements in morphology of Fuel Cell catalysts, especially for ORR. 232,234,236,238,239 This is further explored and demonstrated in the features of the most popular substances in hydrogen fuel cell research and their exemplary publications shown in Table 6. Many of the substances in Table 6 are comprised of the highlighted elements on Figure 13.…”
Section: Figure 11 Publication Trends and Distinct Substances Used By...mentioning
confidence: 98%
See 1 more Smart Citation
“…The application of these materials is diverse, but the literature shows that the main interests are for the increase of surface area, porosity or just general improvements in morphology of Fuel Cell catalysts, especially for ORR. 232,234,236,238,239 This is further explored and demonstrated in the features of the most popular substances in hydrogen fuel cell research and their exemplary publications shown in Table 6. Many of the substances in Table 6 are comprised of the highlighted elements on Figure 13.…”
Section: Figure 11 Publication Trends and Distinct Substances Used By...mentioning
confidence: 98%
“…We suspect this is due to research efforts directed to the Oxygen Reduction Reaction (ORR), which occurs in the cathode of most fuel cells, being one of the major challenges when it comes to reducing cost. [231][232][233][234][235][236][237][238][239] One can also see the interest in tackling this challenge with other concepts, particularly "electrochemical reaction catalysts" and "electrochemical reduction" cluster. Similar to water splitting, the inclusion of concepts such as "nanoparticles" (also reflected on Table 1) and "Surface area" in this blue cluster confirms morphology and surface research as important parameters when optimizing catalysts.…”
Section: Figure 11 Publication Trends and Distinct Substances Used By...mentioning
confidence: 99%
“…55 Benefitting from these advantageous merits, these electrospun nanomaterials can thus work as promising electrocatalysts to largely promote the catalytic activity and efficiency. 56,57…”
Section: Advantages Of Electrospun 1d Nanocatalystsmentioning
confidence: 99%
“…Intermetallic nanocrystals (NCs) are one of the most studied classes of materials for electrocatalysis due to their high electrochemical stability at lower precious metal loadings. ,,, Pt–Co intermetallic face-centered-tetragonal (fct) phase (L1 0 ) NCs have been demonstrated as viable electrocatalysts for the oxygen reduction reaction (ORR). , The ability to perform the ORR with high electrochemical stability while decreasing the Pt loading is of key importance for proton exchange membrane fuel cells (PEMFCs), ,, with the capability of providing a source of clean energy able to compete with fossil fuels . To make PEMFCs economically viable, there is a need to optimize the activity of the catalyst per unit Pt, , also known as the mass activity.…”
mentioning
confidence: 99%
“…We use near-monodisperse Cu-doped PtCo 2 NCs in the intermetallic L1 0 phase as a model system. Copper-doping is known to reduce the barrier associated with the phase transformation. ,, The L1 0 phase is desirable because of simultaneously higher electrochemical stability and lower cobalt leaching during catalysis than the random alloy (A1) phase. , ,,,, Typically, as-synthesized A1 face-centered-cubic (fcc) phase NCs are transformed into intermetallic L1 0 NCs by a thermal treatment that involves temperatures exceeding 400 °C over several hours. ,,,,, During this process, NC aggregation, or sintering, occurs, leading to a decrease in the electrochemically active surface area (ECSA) and resulting in a decrease in mass activity for the ORR. ,,, Several literature reports have attempted to prevent NCs from aggregating during the thermal treatment by anchoring the NCs to the substrate, ,, or by synthesizing the NCs directly in the intermetallic phase. ,, Other methods have demonstrated a monodisperse dispersion of intermetallic NCs; however, these require a specialized technique such as Joule heating or electrochemical dealloying. , So far, no method has shown a complete phase transformation with minimized aggregation.…”
mentioning
confidence: 99%